Management Information System for Maimun Palace Tourism Using Web Engineering and FAST Methods - Zahrina, Nadhilah; Suendri (The IJICS (International Journal of Informatics and Computer Science), 2025)
This study aims to design and implement an event reservation and payment system to support tourism services at Istana Maimun, Medan. The system was developed to simplify the process of event booking, payment, and management for both users and administrators. The development method adopted was a web-based approach using the Laravel framework and MySQL database. System testing was carried out using the black-box method, focusing on functional requirements such as event creation, reservation processing, and payment confirmation. The testing scenarios included valid and invalid inputs to evaluate the system’s ability to handle different cases. The results showed that all core functionalities performed as expected, with correct status updates and validation messages. The payment module successfully processed transactions and displayed accurate order details, including transaction amounts and unique order IDs. In addition, the system effectively prevented duplicate payments and ensured data consistency between reservations and payment records. Based on these findings, the system is considered functionally ready for production use. It can improve operational efficiency and user experience in managing event reservations at Istana Maimun. Future development may focus on integrating additional features such as online ticket verification and mobile application support.